(untitled) (Journal of Engineering Studies and Research, 2023)
In this work was done a fluid dynamic study in an experimental packed reactor using RTD exposing bimodal and modal behavior when it was varied the particle diameter and bed presenting flow channels, dead zones in the vessel and lateness of the material mixture in the equipment. Additionally, using flow pattern models was estimated the chemical conversion with greater approximation to the experimental value. This result could be use in the scaling stages of the process and minimize overdesigns.